Heart failure with mid-range ejection fraction: 3 years after its creation, what do we know? - Eva Isabel Silva Fernandes (2020)
Who are the patients with mid-range ejection fraction? Why did the European Society of Cardiology create this category? Does this new group have differences in its epidemiology and in its response to pharmacological therapy? In this descriptive review we seek to characterize heart failure patients with mid-range ejection fraction, their comorbidities and the way they respond to pharmacological treatment. Although these patients show an intermediate phenotype in terms of sex and age, confirming their status as the "middle brother" between the two classic ejection fraction groups, this class also shows some unique features, such as its particularly high incidence of ischemic coronary disease. While their prognosis brings them closer to patients with preserved ejection fraction, their response to pharmacological therapy appears to be vastly superior to the preserved ejection fraction one. Mid-range ejection fraction patients seem to display significant better outcomes when treated with beta blockers and mineralocorticoid receptor antagonists, however only small and mostly retrospective analysis are available at the moment. Will the next guidelines change the therapeutic approach to this new branch of heart failure? Bigger and better research needs to be conducted and, above all, the medical community needs more time to understand patients with mid-range ejection fraction and heart failure in general. At the end of this review, a question remains: are we labelling our patients the right way?